A Comparative Study on the Higher-Dimensional Transportation Problems: FSTP and MODI - Sultana, Nahid; Alam, H S Faruque; Ray , Ganesh Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2023)
An optimal allocation aids a company to get its desired outcome. Their aims are distributed into two core sections; they want to maximize the profit and also try to minimize the related cost. Transportation cost is one of the unwanted costs for the companies. They want to abate it as well. To cut it down, there are a lot of solving methods developed recently. From the recent developments we choose the two effective methods Faster Strongly Polynomial method (FSTP) and the Modified Distribution method worked on Vogel's Approximation Method (VAM-MODI) to find the best one. On our selected higher-dimensional problems, the findings show us that FSTP is best if we compare the number of steps, but concerning the short execution time, VAM-MODI performs well. GANIT J. Bangladesh Math. Soc. 43.1 (2023) 37- 48